Rancangan automatic change over switch (ACOS) di bandara lasondre - Chanif Nasrudin; Feti Fatonah; Riyanto Saputro (Journal Transformation of Mandalika, e-ISSN: 2745-5882, p-ISSN: 2962-2956, 2026)
The reliability of the airport's electrical power supply system is a crucial factor in ensuring the safety and smooth operation of flights. Lasondre Airport still uses a manual power source switching system through a Change Over Switch (COS), resulting in frequent delays in the switching process from PLN to a generator. This can disrupt landing and take-off activities, as well as navigation systems and flight support equipment that require an uninterrupted power supply. This research aims to develop an Automatic Change Over System (ACOS) capable of performing power source switching automatically, quickly, and reliably using a Socomec 125 A ATS, DSE 7420 controller, LY2N relay, and H3CR Time Delay Relay (TDR). The system works by detecting PLN failures, automatically turning on the generator, transferring the load to the backup source, and returning the load to PLN when conditions are normal. The implementation of ACOS is expected to improve the continuity of electricity supply according to CASR Part 139 standards, however, the analysis results show that the capacity of the 50 kVA generator is still insufficient for the total load, requiring an increase in capacity or separation of essential and non-essential loads